Clinicopathological, gene expression and genetic features of stage I lung adenocarcinoma with necrosis. (September 2021) - Oiwa, Hiroaki; Aokage, Keiju; Suzuki, Ayako; Sato, Kei; Kuroe, Takashi; Mimaki, Sachiyo; Tane, Kenta; Miyoshi, Tomohiro; Samejima, Joji; Tsuchihara, Katsuya; Goto, Koichi; Funai, Kazuhito; et al.
Highlights: Tumor necrosis was independently associated with higher risk of recurrence. The presence of tumor necrosis itself is an important predictive indicator. The cases with necrosis have distinct clinicopathological and genetically features. Abstract: Objectives: The purpose of this study was to investigate the clinicopathological, gene expression and genetic features of stage I lung adenocarcinoma with necrosis. Methods: We retrospectively reviewed 521 cases with pathologic stage I lung adenocarcinoma resected by lobectomy and lymph node dissection. We calculated the ratio of tumor necrotic area by digital image analysis and investigated the relationship between tumor necrosis and prognosis. Furthermore, we analyzed the differentially expressed genes between cases with and without necrosis using The Cancer Genome Atlas Lung Adenocarcinoma (TCGA-LUAD) dataset. Using whole exon sequencing data (n = 97), we examined whether tumor necrosis correlates with single nucleotide variants (SNVs) and driver mutations. Results: Eighty four (16%) cases of the study cohort had tumor necrosis. The presence of necrosis significantly correlated with poorer prognosis (5-year overall survival: 91.9% vs. 75.4%, p < 0.001; 5-year recurrence-free survival: 86.0% vs. 59.0%, p < 0.001); however, the ratio of necrotic area did not correlate with prognosis. In multivariable analysis, invasive component size, vascular invasion, and tumor necrosis were independently associated with a higher risk of recurrence (hazard ratio, 1.652; 95% confidence interval, 1.033–2.641; p = 0.036). Gene expression analysis of TCGA stage I lung adenocarcinoma revealed enrichment of biological processes, such as cell cycle and response to hypoxia, in cases with necrosis. The cases with tumor necrosis had more SNVs than those without tumor necrosis (p = 0.027), especially in smokers. Conclusion: Stage I lung adenocarcinoma with tumor necrosis has worse prognosis than that without, and has distinct clinicopathological features in terms of gene expression and genetic features.